PENGARUH BUDAYA LOKAL TERHADAP PELAKSANAAN RESTORATIVE JUSTICE DI INDONESIA - Nasaruddin; Aly Rizky; Abdul Jabal Rahim (Journal Publicuho, 2024)
Restorative Justice (RJ) is an approach in the criminal justice system that focuses on repairing relationships between offenders, victims, and the community, differing from the conventional system that emphasizes punishment. In Indonesia, RJ faces unique challenges due to the diversity of local cultures that influence conflict resolution and the enforcement of laws. Cultural values such as mutual cooperation, deliberation, and customary peace can enrich the RJ process but also encounter challenges when they conflict with human rights principles or national laws. This research aims to explore the impact of local culture on the process and outcomes of RJ in resolving criminal cases in Indonesia. The methods employed include legislative, conceptual, and case approaches with prescriptive analysis. The findings indicate that the integration of local culture, such as deliberation and involvement of traditional leaders, enhances the effectiveness of RJ and victim satisfaction. However, challenges such as cultural value differences and national legal frameworks need to be addressed.